Use of winter cover crops improves maize productivity under reduced nitrogen fertilization: a long-term study - Piva,Jonatas Thiago (2021)
ABSTRACT The objective was to evaluate the effect of winter cover crops on the agronomic performance of maize during five crop seasons in a clayey Inceptisol with reduced mineral nitrogen (N) inputs. The treatments were seven single cover crops: white oats (Avena sativa L.), black oats (Avena strigose Schreb.), ryegrass (Lolium multiflorum L.), canola (Brassica napus L.), vetch (Vicia sativa L.), fodder radish (Raphanus sativus L. and red clover (Trifolium pratense L.); a mix (black oats + vetch and a fallow. During summer, in succession to the cover crops, maize was grown under no-tillage. The attributes were evaluated in two stages of maize development: flowering (morphological components and physiological maturation (yield components). Differences in morphologica and yield variables were observed in all crop seasons, with emphasis on grain yield, number of grains per row (NGR and ear length (EL). The use of vetch showed greater contribution to the development of maize in relation to the other cover crops used, promoting an increase in stem diameter (SD), E and NGR in all crop season and directly reflecting in higher grain yield. On the other hand, when maize was grown under cover crops commonly used in southern Brazil, such as ryegras and white oats, the yield was similar to fallow. The results showed that vetch promoted higher maize yields, probably by N mineralization and reinforce the hypothesis that cover crops in the off-season can aggregate benefits to crops in succession, especially in terms of nutrition.